Technical Analysis of Directional Movement Index Indicator, Ichimoku Kinko Hyo Towards Stock Price Movements in Indonesia's Finance Sector - Setiawan, Muhammad Fakhri; Imronudin, I (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research aims to provide recommendations related to investment or trading momentum using technical analysis based on two indicators, namely the Directional Movement Index (DMI) and Ichimoku Kinko hyo. The research population consists of stock price movements of financial companies listed on the Indonesia Stock Exchange in the 2023 period. Stock price movement data is analyzed using the TradingView app. The method used is technical analysis, where Ichimoku Kinko hyo serves to identify stock price trends at a certain time, and DMI is used to measure trend strength as well as provide signals related to investment momentum. The data is analyzed in a descriptive analysis, with visualizations of trends and momentum generated through TradingView. The results show that the combination of Ichimoku Kinko hyo and DMI is effective in predicting stock price trends and providing signals for investment decision-making. Ichimoku Kinko hyo charts the market trend clearly, while the DMI assesses the strength of the trend and provides the right momentum signal to buy or sell. This study makes an important contribution to investors and traders in the stock market, in determining the right time to make a buy or sell decision based on the strength of the trend and momentum. Thus, the combination of these two indicators can increase the accuracy of trading decision-making in the financial stock sector on the IDX.